Islam Sebagai Kekuatan Politik Perspektif Umar bin Khatab - idkham; Afrizal; Sawaluddin (CV Kalimasada Group, 2024)
This text descriptively discusses the political policies of Umar bin Khattab in governing the state. Umar's leadership lasted for about 10 years, yet under his rule, the government expanded rapidly due to the stable political conditions and the continuity of leadership from Abu Bakr Ash-Shiddiq. Khalifah Umar proved to be an effective administrator, establishing governmental institutions and policies that separated the interests of the political elite from those of the general population. Umar is known for his groundbreaking policy of dividing the state into provinces, each governed by a designated governor. He also continued the expansion of the empire to various regions, including the Arabian Peninsula, Palestine, Syria, Iraq, Egypt, Persia, and Rome, strengthening and empowering Islam, based on the principles of the Qur'an and Sunnah. His knowledge and innovations in addressing poverty, as well as his ability to optimize the state's wealth and resources, ensured that the society of his time lived in peace, prosperity, and well-being.